Targeting mutant KRAS with CRISPR-Cas9 controls tumor growth - Kim, Wonjoo; Lee, Sangeun; Kim, Han Sang; Song, Minjung; Cha, Yong Hoon; Kim, Young-Hoon; Shin, Jeonghong; Lee, Eun-Seo; Joo, Yeonsoo; Song, Jae J.; Choi, Eun Ju; Choi, Jae W.; et al.

(untitled) (Genome Research, 2018)
KRAS is the most frequently mutated oncogene in human tumors, and its activating mutations represent important therapeutic targets. The combination of Cas9 and guide RNA from the CRISPR-Cas system recognizes a specific DNA sequence and makes a double-strand break, which enables editing of the relevant genes. Here, we harnessed CRISPR to specifically target mutant KRAS alleles in cancer cells. We screened guide RNAs using a reporter system and validated them in cancer cells after lentiviral delivery of Cas9 and guide RNA. The survival, proliferation, and tumorigenicity of cancer cells in vitro and the growth of tumors in vivo were determined after delivery of Cas9 and guide RNA. We identified guide RNAs that efficiently target mutant KRAS without significant alterations of the wild-type allele. Doxycycline-inducible expression of this guide RNA in KRAS-mutant cancer cells transduced with a lentiviral vector encoding Cas9 disrupted the mutant KRAS gene, leading to inhibition of cancer cell proliferation both in vitro and in vivo. Intra-tumoral injection of lentivirus and adeno-associated virus expressing Cas9 and sgRNA suppressed tumor growth in vivo, albeit incompletely, in immunodeficient mice. Expression of Cas9 and the guide RNA in cells containing wild-type KRAS did not alter cell survival or proliferation either in vitro and in vivo. Our study provides a proof-of-concept that CRISPR can be utilized to target driver mutations of cancers in vitro and in vivo.